Flood risk vulnerability assessment using GIS and hydraulic modeling, case study of the Fez river watershed, Morocco - Essahlaoui Narjisse; El Ouali Abdelhadi; Rhazi Abdelaziz; Alitane Abdennabi; Ijlil Safae; Mohajane Meriame; Ammari Zakaria; Oumou Abdellah; Khrabcha Abdelali; El Hafyani Mohamed; Essahlaoui Ali; Aouragh My Hachem; et al. (E3S Web of Conferences)
Morocco, like other countries in the world, is threatened by floods. These have become frequent in previous years and the current year (2024). Weather-related floods in the Fez river watershed constitute the natural hazard that threatens property. In this work, we adopted an approach based on the modeling of flow processes using the HEC-RAS model. The main sources of information are topographic map, geological map, hydrometeorological data, digital terrain model (DTM), land use, etc. 2D and 3D hydraulic modeling using HEC-RAS software, allowed the mapping and analysis of floodplains. The HEC-RAS hydraulic modeling tool is used to perform permanent flow simulations and the model input files are developed in GIS software using the HEC-GeoRAS extension. The results of the study further indicate that the Geographic Information System combined with hydraulic modeling are very effective tools for floodplain mapping and analysis. The resulting map is the flood risk map. This useful information can be used to plan and control future floods and will thus help in sustainable land management.